Occupational Injuries and Accidents in Work Environment’s Heat Stress Exposure: A Systematic Review - Rajabali Hokmabadi (Archives of Occupational Health, 2020)
Background: activity in hot environments is among the most common physical dangers in work environments that not only creates diseases resultant from heat which influences on staff’s health but also increases job injuries and accidents. Job injuries, diseases, and reduction in workerschr('39') efficiency in exposure to heat stress have caused increasing anxiety. Most of the study results are demonstrative of diseases as a result of heat and less related to job injuries and accidents. Therefore, the present study aims at reviewing previous studies in the field of job injuries and accidents in exposure to the work environmentchr('39')s heat stress. Methods: this review study has systematically reviewed publications and articles from 2000 to 2019 in databases. Keywords including "heat stress”, “heat strain”, “heat exposure”, “heat wave", "heat injuries”, “job accidents”, “job exposure”, “hot environment” and “air change" have been used and finally, 30 articles included into the study. Results: study articles consist of 29 jobs and 1 military environment. Study occupations consist of one study about military forces, textile, aluminum smelting, cleaners of oil reservoirs, two studies about mineworkers and metal and iron industries, three studies about building workers, four studies about agricultural workers and 15 studies about different occupations. Also, 11 studies conducted in open environments, seven studies in closed environments and 12 others conducted both in open and closed environments. 17 analytical studies, three correlational, cross-sectional, cohort studies, one cohort, and descriptive study and two descriptive-analytical studies have been conducted. Most job injuries and accidents happened during summer and men especially the young have involved in such problems and job injuries and accidents have increased due to extreme temperature increase. Generally, job injuries and accidents include burn, slip, collision with things and collision with mobile things. Conclusion: there is a strong relationship between temperature in hot environments and risk increase in injuries and accidents of work environments which differ based on employeeschr('39') features (such as age, gender, occupation, and industry). However, dominant mechanisms on the happening of such injuries have not been determined yet. It necessitates more expertise to determine especial injuries and accidents happening in hot environments. Policymakers and employers have to be more aware of job injuries and accidents in heat exposure and suitable educational resources have to be provided to prevent such injuries.